The Benefit of An Antioxidant on Atherosclerosis - Clara Yulianti Tarigan (Global Health Science Group, 2020)
Atherosclerosis is a progresif change of artery walls which is marked by fat deposit, leukosit recrutiment and accumulation, foam cells formation, miosit migration and proliferation as well as extracellular matrix deposits which leads to thickening and hardening of artery.The aim of this literature review is to explain about. References which are used in this writing are 17 articles which are collected from PubMed NCBI and google scholar are all published in range of year 2005-2020. The keywords which are used for this literature searching area atherosclerosis, ROS, physical activities, stress oxidative, and antioxidant. The references which have been collected were analyzed by systematic literature review method which include collecting, evaluation, and development of research which certain focii. Atherosclerosis can occur due to excessive physical activities hence may cause the increase of ROS as a result of muscle cells aerobic metabolism process during physical activity. The rise in ROS may cause the inbalance between oxygen and antioxidant leading to stress oxidative. Antioxidant can be used to prevent the occurrence of stress oxidative. Antioxidant is a substance needed for the body to prevent free radicals and prevent the damage caused by it. Some of them are vitamin C and vitamin E as well as other herbal plants such as green tea and noni fruit.